2017
DOI: 10.1080/10803548.2017.1350392
|View full text |Cite
|
Sign up to set email alerts
|

Expert system application for prioritizing preventive actions for shift work: shift expert

Abstract: A thorough literature review is conducted to determine the effects of shift work on workers. Our work indicates that shift work is linked to demographic variables, sleepiness and fatigue, health and well-being, and social and domestic conditions. These parameters constitute the sections of a questionnaire designed to focus on 26 important issues related to shift work. The shift expert is then constructed to provide prevention advice at the individual and organizational levels, and it prioritizes this advice us… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 46 publications
0
3
0
Order By: Relevance
“…For example, researchers built an expert system that identifies the characteristics that contribute to negative effects of shift work and then selects mitigation efforts according to their importance in preventing these negative effects. With a fuzzy analytic hierarchy process model, the shift “expert” prioritizes prevention advice to shift workers at the individual and organization level [ 73 ].…”
Section: Other Use Cases For Artificial Intelligence and Sleep Medicinementioning
confidence: 99%
“…For example, researchers built an expert system that identifies the characteristics that contribute to negative effects of shift work and then selects mitigation efforts according to their importance in preventing these negative effects. With a fuzzy analytic hierarchy process model, the shift “expert” prioritizes prevention advice to shift workers at the individual and organization level [ 73 ].…”
Section: Other Use Cases For Artificial Intelligence and Sleep Medicinementioning
confidence: 99%
“…Meditation, as a form of mental training, can improve the self-regulation of attention and emotions, mainly including mindfulness meditation and mantra meditation [14]. Many studies have shown that , Meditation can promote the activity of the left prefrontal cortex and other areas of the brain, and has the potential to treat clinical diseases [15].…”
Section: Contactless Devicesmentioning
confidence: 99%
“…Table 3. Recent research studies used ES Authors Years ES applications [52] 2016 Evaluation of the performance of sustainable manufacturing [53] 2016 Material handling equipment selection [54] 2019 [55] 2019 Layout designs [56] 2018 Optimization of Design and Manufacturing Process [57] 2019 Shift work [58] 2015 Machine tool selection [59] 2015…”
Section: Is the Expert System Still Promising?mentioning
confidence: 99%